[Math] Proving the distributive law with natural deduction

formal-proofslogicnatural-deductionproof-theoryproof-writing

I have to prove the following logical equivalence, also known as one of the two distributive laws:

$$
P \vee (Q \wedge R) \equiv (P \vee Q) \wedge (P \vee R)
$$

I have solved the first part, $P \lor (Q \land R) \to (P \lor Q) \land (P \lor R)$, like so:

enter image description here

But now that I'm trying to solve the next part, $(P \lor Q) \land (P \lor R) \rightarrow P \lor (Q \land R)$, I keep getting stuck somewhere with a disjunction elimination where I'm trying to prove something like $P$ with only $Q$ and $(P ∨ Q) ∧ (P ∨ R)$.

So how can I prove $(P \lor Q) \land (P \lor R) \rightarrow P \lor (Q \land R)$ using a proof tree, like shown above? Thanks!

Best Answer

Let $A = (P \lor Q) \land (P \lor R)$ and $B = P \lor (Q \land R)$.

The following is a derivation in natural deduction of $B$ from $A$.

$$ \dfrac{\dfrac{A}{P \lor Q}\land_{e_1} \quad \dfrac{[P]^*}{B}\lor_{i_1} \quad \dfrac{\dfrac{A}{P \lor R}\land_{e_2} \quad \dfrac{[P]^{**}}{B}\lor_{i_1} \quad \dfrac{\dfrac{[Q]^* \quad [R]^{**}}{Q \land R}\land_i}{B}\lor_{i_2}}{B}\lor_e^{**}}{B} \lor_e^* $$

Note that the derivation above is based on two nested applications of the rule $\lor_e$.

From the derivation above you obtain the derivation of $A \to B$ (without assumptions) by adding a $\to_i$ rule as last rule, discharging the two occurrences of $A$.

Related Question